A review of indoor air quality interventions and child neurobehavioral outcomes - Aimée Vester; Patrick H. Ryan; Kimberly Yolton; Jareen K. Meinzen-Derr; Nicholas C. Newman (Pediatric Research, 2026)
Abstract Children are uniquely vulnerable to the neurotoxic effects of air pollution because their brains continue to develop throughout childhood. Indoor air pollution comprises a mixture of several pollutants and is influenced by both indoor and outdoor air pollutant sources. Growing evidence from animal models and epidemiological studies illustrates the adverse effects of air pollutants, especially particulate matter ≤2.5 μm (PM 2.5 ), on cognitive function and academic performance due to its ability to generate oxidative stress and elicit neuroinflammation. Interventions such as air filtration can meaningfully reduce indoor concentrations of pollutants such as PM 2.5 . Given the significant time children spend indoors in home, school, and childcare settings, indoor air quality interventions are apotential tool to mitigate adverse health effects of indoor air pollutants in children. However, most interventional studies of indoor air pollution focus on improving respiratory outcomes, such as asthma. Here, we conducted a narrative review to collate studies on indoor air pollution interventions that assess neurobehavioral outcomes. Ultimately, our goal was to highlight potential future directions for additional interventional studies that may contribute to public health efforts to optimize neurobehavioral outcomes in children. Impact Mounting evidence suggests indoor air pollution presents a public health concern for neurobehavioral outcomes. Children are particularly vulnerable to the adverse effects of indoor air pollution and subsequent neurobehavioral outcomes. While studies illustrate potential benefits of indoor air pollution interventions on respiratory outcomes, less is known about neurobehavioral outcomes. This narrative review adds to existing literature by summarizing studies of indoor air pollution interventions and neurobehavioral outcomes published in the past 20 years. This review discusses potential next steps for future interventional studies on indoor air quality and child neurobehavior.